(untitled) (Revista Apotheke, 2019)
Walter Benjamin had already announced in middle of the XX century the consequences of the development of the image reproduction techniques in the universe of visual arts. In contemporary times, the virtuality of world wide web (www) and the facilities caused by digital printing, has severely impact the universe of independent graphic and editorial arts. A nice example is the proliferation of books and print fairs, in a national and international scope, besides the facilities provided by social media and ecommerce platforms. This paper aims to reflect about indie publishing market, presenting the experiences in handcrafted books. This text also intend to debate about the aura of the publishings, its artisanal production, made one by one, by people, book artists, and not only by machines in industrial automatized process.